EFFECT OF TIME AND TEMPERATURE ON ISOMERIZATION REACTION OF Î-PINENEUSING CATALYST ZR 4+ Nanik Wijayati, Supartono, Nuni Widiarti, Tri Handayani /NATURAL ZEOLITE - Wijayati, Nanik; Supartono, Supartono; Widiarti, Nuni; Handayani, Tri (Sainteknol : Jurnal Sains dan Teknologi, 2016)
Effects of time and temperature on Î±-pinene isomerization reaction using catalysts Zr/natural zeolitewas studied. Characterization of the catalysts include: crystallinity, observed using X-Ray Diffraction, count Zr 4+ carried observed using X-Ray Fluorescence, area and porosity catalyst was observed using the Surface Area Analyzer, and acidity catalyst observed through gravimetric method. Isomerization reaction carried out in a batch reactor with temperature variations 90, 120 and 150 C and reaction time variations of 60, 90, 120, 150 and 180 minutes. Best results of isomerisation in this study was obtained at 150 derajat C with a reaction time of 180 minutes. Kindsof isomer obtained was observed using GCMS. Catalyst characterization results indicate that modification of the catalyst by cation Zr increases the acidity from 2.76 to 6.64 mmol/g and does not damage the crystal structure significantly. The highest product conversion in this research is 9.24%, less than the maximum results caused by pre-treatment of the catalyst produces a low area. Thus, temperature and reaction time affect the concentration of Î± pinene isomerization product in addition to the effect of the catalyst used.